Characteristics of the Audit Committee on Delay in Audit Reporting - Jesni Jesni; Santi Yopie (LPPM Universitas Trunojoyo Madura, 2023)
The occurrence of audit delay is related to the characteristics of the audit committee which is reflected in various indicators. This study aims to analyze the effect of the characteristics of the audit committee consisting of the Audit Committee Chair with accounting expertise, the Audit Committee with accounting expertise, the Audit Committee with non-accounting expertise, the Independence of the Audit Committee, the Size of the Audit Committee, and the Audit Committee Meetings on late reporting of reports. audited financial statements for companies listed on the IDX for 2017-2021. The sampling technique used purposive sampling with a total of 1,211 data processed from 243 companies. Data processing was performed using panel data regression assisted by the e-views application version 10. The results showed that the five independent variables and three control variables used had no significant effect on audit delay, while the audit committee meeting variable had a significant positive effect on audit delay. The implication of this finding is that it is necessary to organize more effective and efficient audit committee meetings so as not to hinder the audit report process which can extend the audit delay that occurs.